2018
DOI: 10.3892/ol.2018.8000
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‑associated fibroblasts induce epithelial‑mesenchymal transition through secreted cytokines in endometrial cancer cells

Abstract: Endometrial cancer (EC) is the most common malignant gynecological disease. Cancer-associated fibroblasts (CAFs) serve an important role in the development and progression of EC through epithelial-mesenchymal transition (EMT). The aim of the present study was to examine the association between CAFs and EMT, and the possible mechanisms of action. Firstly, the CAFs and normal fibroblasts (NFs) were isolated and cultured, then an immunofluorescence assay was performed to analyze the purity and level of activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…Fibroblasts are non-epithelial cells with a likely mesenchymal lineage origin, and several mesenchymal markers such as vimentin and fibronectin, are often used to detect CAFs. 8,27 CAFs enhance metastasis potential by inducing EMT in several types of cancer, such as gastric cancer, endometrial cancer and lung cancer cells, 11,28,29 suggesting the mesenchymal status is a key factor for CAFs' function. Interestingly, Shi et al reported that enforced expression of c-Myc in fibroblasts increase the expression of epithelial markers and reduce the expression of mesenchymal markers, lead to the mesenchymalepithelial transition (MET) in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts are non-epithelial cells with a likely mesenchymal lineage origin, and several mesenchymal markers such as vimentin and fibronectin, are often used to detect CAFs. 8,27 CAFs enhance metastasis potential by inducing EMT in several types of cancer, such as gastric cancer, endometrial cancer and lung cancer cells, 11,28,29 suggesting the mesenchymal status is a key factor for CAFs' function. Interestingly, Shi et al reported that enforced expression of c-Myc in fibroblasts increase the expression of epithelial markers and reduce the expression of mesenchymal markers, lead to the mesenchymalepithelial transition (MET) in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…41 CAFs induce epithelial tumorigenesis in normal but initiated/immortal prostate epithelial cells when co-cultured with normal fibroblasts. 53 CAFs induce EMT, CXCR4, and IL-6 receptor expression through the monoamine oxidase A/mammalian target of rapamycin (mTOR)/hypoxia-inducible factor (HIF)-1a in the PC3 PC cells. 53 Monoamine oxidase promotes EMT and PC metastasis by stabilizing the hypoxia-associated gene HIF1a and inducing hypoxia through oxidative stress.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…53 CAFs induce EMT, CXCR4, and IL-6 receptor expression through the monoamine oxidase A/mammalian target of rapamycin (mTOR)/hypoxia-inducible factor (HIF)-1a in the PC3 PC cells. 53 Monoamine oxidase promotes EMT and PC metastasis by stabilizing the hypoxia-associated gene HIF1a and inducing hypoxia through oxidative stress. 53,54 The monoamine oxidaseedependent regulation of EMT is activated through the HIF-1a/VEGF/forkhead box A1 (FOXA1)/TWIST1 pathway, and a knockdown of monoamine oxidase led to a reduction in the proliferation and metastasis in xenograft PC mouse models.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations